1998
DOI: 10.1128/jb.180.5.1323-1330.1998
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Diversity, Predicted Two-Dimensional Protein Structure, and Epitope Mapping of Neisserial Opa Proteins

Abstract: The sequence diversity of 45 Opa outer membrane proteins fromNeisseria meningitidis, Neisseria gonorrhoeae,Neisseria sicca, and Neisseria flava indicates that horizontal genetic exchange of opa alleles has been rare between these species. A two-dimensional structural model containing four surface-exposed loops was constructed based on rules derived from porin crystal structure and on conservation of sequence homology within transmembrane β-strands. The minimal continuous epitopes recognized by 23 monoclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 50 publications
(79 reference statements)
4
65
0
Order By: Relevance
“…NspA displays high sequence homology with the neisserial Opa proteins, especially the membrane-spanning b -barrel domain. Based on this homology, Vandeputte-Rutten et al (2003) argue that it is likely that the fourth strand in the predicted topology model of Malorny et al . (1998) has to be shifted towards the extracellular side by eight residues (this recent finding was integrated in Figs 2, 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NspA displays high sequence homology with the neisserial Opa proteins, especially the membrane-spanning b -barrel domain. Based on this homology, Vandeputte-Rutten et al (2003) argue that it is likely that the fourth strand in the predicted topology model of Malorny et al . (1998) has to be shifted towards the extracellular side by eight residues (this recent finding was integrated in Figs 2, 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…No binding to CEACAM3, 6 and 8 was observed. For Malorny et al ., 1998) of OpaA127, OpaB128, OpaD126 and OpaJ129. Identical amino acids within the hypervariable regions mutated in this study present in all four sequences are indicated in bold and underlined.…”
Section: The Four Opa Proteins Derived From H44/76 Are Invasion Assocmentioning
confidence: 99%
“…The anti-Opa rabbit antiserum was produced by the following procedures: two peptides, STVSTDYFRNIRAHSI and HNWGRLENTRFKTHE, both of which correspond to the conserved amino acids of the outer face of the Opa protein (Malorny et al, 1998), were customized by Operon Biotechnologies (Japan). An antiserum specific for the oligopeptides was obtained by immunization of rabbits with the peptides coupled to keyhole limpet hemocyanin using m-maleimidobenzoyl-N-hydroxysuccinimide ester (MBS).…”
Section: Production Of Anti-pilc Rabbit Antiserum and Anti-opa Rabbitmentioning
confidence: 99%
“…If necessary, alignments were edited manually by placing gaps such that they increased DNA sequence similarities. The percentage uniformity, defined as the percentage of the most frequent nucleotide at each position (excluding gaps introduced by the alignment), was determined with the program PsFind (Malorny et al, 1998). The percentage diversity is 100 minus the percentage uniformity.…”
Section: Dna Sequence Analysismentioning
confidence: 99%